Observing bees and wasps: Why surveys and monitoring programs are critical and how they can improve our understanding of these beneficial hymenopterans - Jason Graham; Joshua Campbell; Alexandra Tsalickis; Cory Stanley-Stahr; James Ellis (Journal of Pollination Ecology, 2023)
Flower-visiting bees and wasps (Hymenoptera: Apoidea, Pompiloidea, Scolioidea, Tiphioidea, and Vespoidea) provide essential services in agricultural and urban systems, and ecological functions in natural ecosystems. Understanding the population trends, resource requirements and preferences, ecological challenges, and how to manage these species better requires increased surveys and standardized monitoring efforts for both groups. A monitoring program performed at various scales that provides ecological data is a prerequisite to managing either bees or wasps for conservation or crop pollination purposes. Methods to survey and monitor bees and wasps can be accomplished by a variety of means, depending on the researchers’ aims and goals. Herein, we discuss the importance of 1) evaluating populations of threatened and endangered bee and wasp species, 2) detecting and identifying pollinators of crops, 3) identifying and managing wasp species for use as biological control agents, 4) surveying the ranges of non-native bees and wasps, and 5) utilizing bees and wasps as biological indicators. We also discuss strategies for the selection of surveying and monitoring tools and methodologies best suited to specific goals and situations in beneficial Hymenoptera research. Our hope is that this review will lead to additional bee/wasp survey and monitoring programs and assist researchers with selecting tools and methodologies for the purpose of better understanding these beneficial insects.